GENRE OF APPLICATION DESCRIPTION ON GOOGLE PLAY STORE; A FUNCTIONAL LINGUISTIC STUDY - Jotika Purnama Yuda; Desi Wulandari; Intan Mustika Sari; Yanuaria Kukuh Perwira; Agus Dwi Priyanto; Karlina Denistia (Haluan Sastra Budaya, 2023)
Startups are growing massively at the national and international level. Many applications with similar features are available in application markets. This demands application developers to present their competitive advantage to convince users to download and use their applications. This study used a qualitative descriptive method with functional systemic linguistic approach to identify the elements that make up the genre of application description. The data in this study are application descriptions from the 10 best startups according to startupranking.com. The data, in the form of clauses, were analyzed based on three language metafunctions, namely ideational, textual and interpersonal. The results of this study indicate that there are certain patterns used by the application descriptions of the 10 best startups in the world. The most common linguistic elements found are: the use of process materials to describe experiences in using applications; the use of relational attributive processes to provide assessments and descriptions of applications; the use of rhemes without themes and residues without subjects in imperative sentences that aim to invite readers to download applications; the use of textual themes which are manifested in conjunctions; and some interpersonal themes in the form of rhetorical interrogative sentences.